Perlindungan Hukum Bagi Konsumen Terhadap Kerusakan Benda Gadai Pada Lembaga Gadai Swasta: (Studi Kota Mataram) - Yudhi Arisanjaya; Muhammad Sood (Bagian Hukum Bisnis Fakultas Hukum Universitas Mataram, 2023)
The purpose of this study is to analyze the legal standing of private pawning institutions in the legal system in Indonesia, analyze the legal relationship between the parties and private pawning institutions and consumers, and analyze the legal protection for consumers against pawned objects damaged in private pawn institutions. The research method uses normative-empirical legal research, which uses a statute approach and conceptual approaches. Based on the results of the study, it has been found that private pawnshops, according to OJK Regulation Number 31/POJK.05/2016 concerning pawn business, the company should have legal entities and permission from the OJK. This is for supervision from the OJK to the pawn business. Then for a consumer that damaged their goods during the pledge agreement, the private pawn business will give compensation according to the object's value. If consumers get protection and they feel comfortable, then an equal between the parties is created.